"Wait for a permanent contract": The temporal politics of (in)fertility as an early career researcher. (December 2021) - Hughes, Sarah M
The impetus for this intervention comes from my own experiences of advice to 'wait for a permanent contract' before trying to conceive a child. I contend that this considerate guidance, frequently given to Early Career Researchers, nonetheless re-inscribes a linear capitalist temporality, and that there is a need to resist this binding of the temporalities of (in)fertility to the metrics of the neoliberal academy. I suggest that to promote 'waiting' negates the nonlinear, everyday and intimate politics of our varied, embodied experiences of (in)fertility. It is also grounded within problematic assumptions: first, that waiting is linear; that we will arrive at a permanent job in the future, if we persist with the present; and second, that our (in)fertility is known to us, that we are able to, and will, make a rational decision to conceive a child. These are pervasive assumptions with deeply personal implications. Moreover, they are compounded by the short-term contracts, and expectations of institutional mobility that characterise many experiences of UK academia. My hope for this piece is that it invites geographers to further explore embodied politics of (in)fertility.